2014
DOI: 10.1111/ajt.12530
|View full text |Cite
|
Sign up to set email alerts
|

Waitlist Priority for Hepatocellular Carcinoma Beyond Milan Criteria: A Potentially Appropriate Decision Without a Structured Approach

Abstract: Due to the risk of waitlist dropout from tumor progression, liver transplant candidates with hepatocellular carcinoma (HCC) within Milan criteria (MC) receive standardized exception points. An expansion of this process to candidates with HCC beyond MC has been proposed, though it remains controversial. This study sought to better define the utilization of exception points in candidates with HCC beyond MC and the associated outcomes. We reviewed all nonstandardized HCC applications that underwent formal regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Higher dropout rates have also been reported previously in patients with HCC beyond the traditional criteria [29,30]. Both AFP and tumor progression (tumor biological factors), but not tumor burden (size and numbers) were independently associated with dropout.…”
Section: Discussionsupporting
confidence: 67%
“…Higher dropout rates have also been reported previously in patients with HCC beyond the traditional criteria [29,30]. Both AFP and tumor progression (tumor biological factors), but not tumor burden (size and numbers) were independently associated with dropout.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, Bittermann et al (17) demonstrated that expanding indication for LT in HCC patients beyond Milan may be secure in terms of five-yr mortality when specific factors of tumor biology are taken into account and a strict surveillance of patients on the waiting list is performed.…”
Section: Discussionmentioning
confidence: 99%
“…hepatopulmonary syndrome (10)) or consensus recommendations (i.e. primary sclerosing cholangitis and recurrent bacterial cholangitis (11) or hepatocellular carcinoma beyond Milan criteria (12)) for allocating exception points, the data used to award such points and the compliance with guidelines or recommendations are suboptimal. The goal of this study was to evaluate the current POPH exception policy and its implementation.…”
Section: Introductionmentioning
confidence: 99%